Analisis Faktor-Faktor yang Mempengaruhi Persepsi Masyarakat dalam Pembangunan Hutan Tanaman Rakyat pada KPH Gedong Wani - Dian Nova Yanti; Irwan Sukri Banuwa; Rahmat Safe’i; Christine Wulandari; Indra Gumay Febryano (Jurnal Hutan dan Masyarakat, 2017)
One effort to reduce environmental damage is the launching of the Social Forestry Program by the Ministry of Environment and Forestry. One such program is Community Plantation Forest (HTR). Farmers' perception of a program is the main basis for the willingness to participate in a program. The purpose of this study are: 1) Knowing the perception of the community, and 2) Knowing the factors that affect the public perception of the HTR development program in KPH Gedong Wani. The research was conducted in Sinar Ogan Village, Srikaton, Jati Indah, Jati Baru, and Budi Lestari, which is the recipient village of IUPHHK-HTR. Sampling technique using stratified random sampling and obtained as many as 95 respondents by interview method. To know the factors that influence perception using multiple regression. The results of this study show the public perception on the development of HTR in the medium category. Factors that have significant effect on public perception are formal education, informal education, HTR land area, monthly income, availability of information, and intensity of counseling.